Health Risks Due to Co-Exposure to Noise and Respirable Crystalline Silica Among Workers in the Open-Pit Mining Industry—Results of a Preliminary Study - Iryna Myshchenko; Małgorzata Pawlaczyk-Luszczynska; Adam Dudarewicz; Alicja Bortkiewicz (Toxics)
Occupational exposure to carcinogenic respirable crystalline silica and noise requires a deeper understanding and an assessment of the possible health risks caused by their combined action. Data on individual exposure to respirable crystalline silica (RCS) and occupational noise (ON) was collected among 44 open-pit miners. The study group was divided into two groups according to the job tasks performed. The individual exposure, exceeding of maximum admissible concentration/intensity, and predicted hearing thresholds (HTs) (according to ISO 1999:2013) were compared between the groups directly participating in the technological process (group 1; N = 23) and performing auxiliary, supervising, or laboratory activities (group 2; N = 21). All the analysed indices were significantly higher for group 1; therefore, the job category may predict ON and RCS exposure among open-pit miners. A statistically significant relationship (rs = 0.66, p < 0.05) was found between the time-weighted average (TWA) 8 h RCS and individual daily noise exposure levels. Exposure to noise in the course of employment causes the risk of hearing impairment (mean HTs for 2, 3, and 4 kHz > 25 dB) up to 74% and 4.4% (in the case of groups 1 and 2, respectively). Further studies are needed before conclusions concerning the effects of co-exposure to ON and RCS on open-pit miners can be made.